Using Properties of Discrete Rocks to Optimize Backfiling - V. I. Golik; Xuan Nam Bui; S. A. Maslennikov; V. I. Anischenko (Горные науки и технологии, 2019)
Backfilling optimization is carried out through the use of discrete rock properties. A new line of the process improvement is based on the phenomenon of performance of residual rock strength when jamming in the process of underground mining of deposits within faulted rocks. The research is aimed at reducing costs of backfilling while ensuring the work safety. The goal is achieved by comparing backfilling options depending on the formation of rock natural self-supporting arch. The study is based on the provisions of structural mechanics and continuum mechanics using the phenomenon of performance of residual rock strength due to rock jamming. The backfilling concept has been formulated. Information on geological structure of the studied rocky ore deposit of complicated tectonic structure and the roles of tectonic framework in the behavior of the ore-hosting rock mass in the course of opening by mine workings are presented. The findings of the study of the rock mass condition with determination of characteristic geotechnical domains are presented. Variants of the ore-hosting rock mass behavior are considered depending on natural jamming of elementary structural rock blocks within the arch. The possibility of combining sealing and setting-mix backfilling methods has been clarified. The area of the research findings application in mineral underground mining is recommended. The determination of dangerous displacement area boundaries in rock mass using the mechanism of discrete rock jamming allows achieving higher mining effectiveness while ensuring mining safety. The study results can be used in underground mining of minerals.